Differential induction of proto-oncogene expression and cell death in ocular tissues following ultraviolet irradiation of the rat eye. Issue 2 (1st February 1999) - Wickert, Hannes; Zaar, Kurt; Grauer, Andreas; John, Markus; Zimmermann, Manfred; Gillardon, Frank
Abstract : BACKGROUND/AIMS: Ultraviolet (UV) irradiation of mammalian cells in culture evokes the transcriptional activation of different proto-oncogenes, among them members of the fos/jun family which are known to play an important role in cell proliferation and differentiation. To investigate in vivo UV induced proto-oncogene expression of irradiated ocular cells, the expression of JunB, JunD, and Egr-1 was analysed in the cornea, lens, and retina. Furthermore, UV radiation is known to induce pleiotrophic events in irradiated cells which include growth arrest, inflammation, and even cell death. In order to determine the type of cell death—for example, apoptosis versus necrosis, sections of UV irradiated rat eyes were further examined for distinct ultrastructural morphology of cell death and DNA fragmentation. METHODS: Eyes of anaesthetised rats were exposed to 1.5 J/cm 2 of ultraviolet radiation (280–380 nm). Animals were perfused 6 and 16 hours after irradiation and tissue sections of enucleated bulbi were processed for light and electron microscopy. RESULTS: Under control conditions, Jun B was constitutively expressed in numerous superficial cells but also in scattered basal cells of the corneal epithelium. After UV exposure JunB expression was massively upregulated in many cells of the basal cell layers of the corneal epithelium, although during the entire experiment, both the corneal stroma and endothelium were JunB negative. In contrast, Egr-1 was expressed exclusively in lens epithelium showing only a faint expression pattern under control conditions. However, Egr-1 expression increased after UV exposure, so that many Egr-1 positive cells of the lens epithelium could be found several hours after UV illumination. JunD was expressed in single cells of both the ganglion cell layer and the inner nuclear layer of the retina, a pattern of expression which did not change after UV exposure. Regarding the type of cell death, features of apoptosis were only occasionally present in scattered superficial cells of the corneal epithelium of control eyes. After UV exposure, however, morphological signs of apoptosis and TUNEL positive cells were visible both in the stroma and epithelium of the rat cornea. In contrast, UV irradiated lens epithelial cells exhibited features typical of necrosis. The corneal endothelium and the retina did not show any indications of morphological changes indicative of cell death after UV irradiation. CONCLUSION: Each proto-oncogene encoded protein was found to be expressed in a tissue specific manner and UV irradiation differentially modulates the expression pattern of these transcriptional regulatory proteins. This temporospatial expression pattern of these proteins is accompanied by two morphologically distinct types of cell death in the cornea and lens after UV irradiation.